Developing the PATRIOT Learning Model to Enhance Narrative Writing Skills of Elementary Students: A Research and Development Approach - Rima Rikmasari; Vismaia Damaianti; Udin Saepudin Sa'ud (AL-ISHLAH: Jurnal Pendidikan, 2025)
Many elementary students in Indonesia face challenges in developing writing skills, particularly in generating ideas, organizing coherent paragraphs, and applying language conventions. These difficulties often result in low writing performance, especially in narrative tasks. This study addresses the need for an effective instructional model to support students in overcoming these challenges. This study aimed to examine the effectiveness of the PATRIOT learning model in enhancing narrative writing skills among fifth-grade students. Employing a Research and Development (RD) approach, the model was developed using the ADDIE framework. The implementation involved three experimental classes from different schools in Bekasi City. Data were collected through essay-writing tasks assessed using a validated rubric, measuring content, organization, language use, and mechanics. Quantitative analysis was conducted using SPSS 27, including normality tests and paired sample t-tests. Findings indicate a significant improvement in students’ writing performance after the implementation of the PATRIOT model. T-test results showed statistically significant differences between pre-test and post-test scores across all experimental classes (p 0.005). Students demonstrated notable progress in idea generation, text structure, and language accuracy. The results suggest that the PATRIOT learning model effectively enhances elementary students’ narrative writing skills through its structured, contextual, and student-centered approach. It also offers practical steps that can be adopted by teachers to improve literacy outcomes. The PATRIOT model presents a promising alternative instructional strategy for improving writing competence at the elementary level, particularly in narrative writing contexts.